The impact of school resource officer interaction on students’ feelings about school and school police - Theriot, Matthew Thomas (Crime & delinquency, 2016)
School resource officer (SRO) programs that place sworn law enforcement officers at schools are a popular violence prevention strategy. Despite widespread implementation, little is known about the impact of interacting with these officers on students’ attitudes about SROs and feelings of school connectedness. The purpose of this study was to evaluate the impact of SRO interaction on the attitudes and feelings of 1,956 middle and high school students at 12 schools in one school district. Multivariate analyses showed that more SRO interactions increased students’ positive attitudes about SROs yet decreased school connectedness. Overall, the results suggested a complex relationship between SRO interactions, students’ attitudes, and experiences with school violence. The implications of these results and strategies for how officers can contribute to a positive school environment are discussed.